Performance Analysis in the Finance Sub-Section of the Industry and Trade Office of North Sumatra Province - Rifta Alvira; Muhammad Arif (Penerbit Jurnal Indonesia, 2022)
Employee performance is important for the world of work, one of which is in government agencies because employee performance definitely reflects the performance of the agency as well. Agencies will greatly benefit from good employee performance because they can achieve organizational goals to the maximum. With good employee performance, agencies can carry out their duties properly in order to be able to provide the best service for the community. This research was conducted to fulfill one of the tasks of the internship activity carried out by the author for one full month at the Department of Industry and Trade of North Sumatra Province. This study uses a qualitative descriptive method which emphasizes the process aspect of an action that is seen as a whole. The data used in this study is primary data which was carried out by field observations and interviews. The results of this study indicate that the performance of the employees in the finance department is very good, there is a separation of duties from each sub-section which makes employees have maximum work responsibilities in their fields.